2012
DOI: 10.1016/j.jaci.2012.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Steroid requirements and immune associations with vitamin D are stronger in children than adults with asthma

Abstract: Background the effects of serum vitamin D status on atopy, steroid requirement and functional responsiveness to corticosteroids in children vs. adults with asthma have not been studied systematically. Objective to explore age-specific effects of vitamin D in asthma. Methods serum vitamin D levels were examined in a prospective study of adults and children (102 normal controls and 103 asthmatics). Peripheral blood mononuclear cells (PBMC) were cultured for 3h +/−100nM dexamethasone (DEX) and the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 24 publications
4
76
4
1
Order By: Relevance
“…A third case-control study involving children and adults reported a non-significant difference in 25(OH)D levels between 103 asthmatic patients and 102 controls. This study, however, showed a significant inverse association between vitamin D and serum IgE, as well as vitamin D and daily inhaled corticosteroid dose in the pedia tric asthma group only (17) . Among the non casecontrol studies that reported significant inverse correlation with asthma severity, one study evaluated 616 asthmatic patients (13) , another studied 75 asthmatic patients (14) , whereas a third study investigated 86 asthmatic patients (16) .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…A third case-control study involving children and adults reported a non-significant difference in 25(OH)D levels between 103 asthmatic patients and 102 controls. This study, however, showed a significant inverse association between vitamin D and serum IgE, as well as vitamin D and daily inhaled corticosteroid dose in the pedia tric asthma group only (17) . Among the non casecontrol studies that reported significant inverse correlation with asthma severity, one study evaluated 616 asthmatic patients (13) , another studied 75 asthmatic patients (14) , whereas a third study investigated 86 asthmatic patients (16) .…”
Section: Discussioncontrasting
confidence: 70%
“…Goleva et al (17) reported a significant inverse correlation between serum IgE and serum vitamin D levels in pediatric patients with asthma but not in adult asthmatic patients. They also found significant associations between serum vitamin D levels and vitamin D-regulated targets and the patients ' steroid responses in vitro, as well as steroid requirements in pediatric asthmatic patients but not in the adult asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have pointed out striking links in populations between vitamin D deficiency and asthma severity or requirements for anti-inflammatory medication (27)(28)(29)(30). In previous studies investigating the immunological basis of this relationship, we have shown that 1 α,25-dihydroxyvitamin D3…”
Section: Introductionmentioning
confidence: 73%
“…This arises in part from studies demonstrating that patients with poorly controlled asthma and/or poor responsiveness to corticosteroid have significantly reduced vitamin D, at least as assessed by the circulating precursor 25-hydroxyvitamin D3 (27)(28)(29)(30)47). We and others have previously demonstrated an association with 25(OH)2D3 status and airways smooth muscle mass (27,28,48).…”
Section: Nanzer Et Al 15mentioning
confidence: 98%
“…Дефіцит ві-таміну D сприяє розвитку БА в дітей [7]. Зниження рівня 25(OH)D 3 у крові пов'язане з більш високими шансами загострення БА [3].…”
Section: îáãîâîðåííÿ òà âèñíîâêèunclassified